Auditoría interna como sistema de control y su incidencia en las actividades económicas de la empresa servipaxa s.a., cantón Quevedo, año 2012 - Álvarez Arévalo, Janina Teresa (2015)
This research is based on the Internal Audit and Control System and its impact on economic activities Year 2012. Company SERVIPAXA SA, Quevedo Canton, for the execution of this work has raised the following problem formulation How affects an Internal Audit and control system in organizational and economic activities of the company SERVIPAXA SA Canton Quevedo, 2012? The same is justified, because it improves its administrative process - business through the implementation of an internal audit, since this tool will be achieved through economic performance diagnose, assess the degree of compliance with the system and detect administrative failings - financial, in order to know the real situation of the company so that this in turn make the necessary corrections in the organization, planning, management and control procedures. As we General Purpose: To determine the incidence of Internal Audit and control system in the economic activities of the Company SERVIPAXA SA Canton Quevedo, 2012, in which the following specific objectives highlights: Check the level of compliance of the internal control system the company uses SERVIPAXA SA for the development of their business. Detect administrative weaknesses of the company and analyze the economic performance of the company SERVIPAXA SA Canton Quevedo, we can also note that the methodology used for this study was the interview and questionnaire tools used to develop the different independent variables, and the results showed the research were: The company is in a level stable in terms of the internal control system and according to the findings, further it should be noted that according to the vertical analysis and debt and liquidity indicators used, the company encentra in solvency and liquidity to remain positive in the market . Therefore it is suggested to company executives consider the recommendations outlined in this research.